2003
DOI: 10.1093/emboj/cdg249
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated nuclear export of 60S ribosomal subunits and NMD3 in vertebrates

Abstract: contributed equally to this work 60S and 40S ribosomal subunits are assembled in the nucleolus and exported from the nucleus to the cytoplasm independently of each other. We show that in vertebrate cells, transport of both subunits requires the export receptor CRM1 and Ran´GTP. Export of 60S subunits is coupled with that of the nucleocytoplasmic shuttling protein NMD3. Human NMD3 (hNMD3) contains a CRM-1-dependent leucine-rich nuclear export signal (NES) and a complex, dispersed nuclear localization signal (NL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 52 publications
(81 reference statements)
8
132
2
5
Order By: Relevance
“…It has been shown previously that in vertebrates, the large 60 S preribosome subunit is exported via CRM1 and the transport adaptor NMD3 (40,42). We therefore investigated the role of the Nup214-Nup88 subcomplex in 60 S preribosomal nuclear export by studying the localization of GFP-tagged NMD3 (40).…”
Section: Resultsmentioning
confidence: 98%
“…It has been shown previously that in vertebrates, the large 60 S preribosome subunit is exported via CRM1 and the transport adaptor NMD3 (40,42). We therefore investigated the role of the Nup214-Nup88 subcomplex in 60 S preribosomal nuclear export by studying the localization of GFP-tagged NMD3 (40).…”
Section: Resultsmentioning
confidence: 98%
“…In addition, ribosomal gene transcription is regulated through the modulation of the transcriptional apparatus and epigenetic silencing (131). Large and small mature ribosome particles are independently exported to the cytoplasm through an exportin 1 (CRM1) and Ran-GTP-dependent mechanism: export of 60S subunit requires the exchange of complexes Noc1-Noc2 by Noc3-Noc2 (102) and the association with the adaptor shuttling protein NMD3 (142), whereas the 40S needs the heterodimer Noc4p/Nop14p (103). The work by Hinsby et al exploited a machine learning-based predictor of nuclear export signals to analyze the late stage pre-40S complex, suggesting a role also for the human homolog of yeast DIM2p in the targeting and translocation of the late 40S to the cytoplasm (63).…”
Section: Structure Composition and Classical Functions Of The Nuclementioning
confidence: 99%
“…However, terminal rRNA processing of the 18S is cytoplasmic 9 . Furthermore, results from Xenopus have suggested that processing of the 5.8S rRNA from a slightly longer pre-5.8S RNA may occur in the cytoplasm 10 , and S. pombe Eri1 is localized to the cytoplasm2. Mammalian ERI-1 localizes to the nucleolus as well as the cytoplasm 4 (Ansel et al, co-submitted).…”
Section: Online)mentioning
confidence: 99%